Characteristics of a controlled Bragg reflection waveguide with gyrotropic cladding - Demydenko, Y.Y.; Novytskyi, V.V.; Odarenko, Y.M.; Shmat’ko, O.O. (Radiotekhnika, 2024)
A planar Bragg waveguide with a hollow channel, the cladding of which contains periodically arranged dielectric and gyrotropic ferrite layers, has been theoretically investigated. A two-dimensional model of the waveguide is developed taking into account the frequency dependence of the components of the magnetic permeability tensor of gyrotropic layers. Results of numerical calculations (using the finite element method) show regularities of influence of the external magnetic field (pointed to the direction transverse to the longitudinal axis of the structure) induction on the dispersion characteristics of the Bragg waveguide cladding and its spectral characteristics. The orientation of the external magnetic field corresponds to the Voigt configuration. An increase in the induction of the magnetic field leads to a significant transformation of the band gap of the waveguide channel cladding. There is an increase in its width and a shift towards higher frequencies. The results of the calculations of the spectral characteristics indicate the corresponding changes that occur in the frequency band of the Bragg waveguide. It is shown that the increase in the width of the transmission zone of the waveguide occurs mainly in the high-frequency region of the considered part of the spectrum. The calculated spatial distribution of the electric field in the studied structure indicates a high degree of localization of electromagnetic energy in the hollow waveguide channel within its transmission zone. This makes it possible to simplify the model of the studied structure due to the exclusion from consideration of losses in gyrotropic layers. On the basis of controlled Bragg waveguides, a variety of functional devices in the microwave and optical ranges can be developed, the operating characteristics of which change under the influence of an external magnetic field.